2020
DOI: 10.1002/ejhf.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐based differences in biomarkers, health status, and reverse cardiac remodelling in patients with heart failure with reduced ejection fraction treated with sacubitril/valsartan

Abstract: Aims We sought to determine sex‐based differences in biomarkers, self‐reported health status, and magnitude of longitudinal changes in measures of reverse cardiac remodelling among patients with heart failure with reduced ejection fraction (HFrEF, left ventricular ejection fraction ≤40%) treated with sacubitril/valsartan (S/V). Methods and results This was a subgroup analysis of patients initiated on S/V in the Prospective Study of Biomarkers, Symptom Improvement and Ventricular Remodeling During Entresto Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Notably, the value of sacubitril/valsartan treatment for reversing LV remodeling in patients with HFrEF has been confirmed in recent years. 3,22,23 In our study, we found that the degree of TAPSE improvement was closely associated with improvements in LVEF and LVESV after adjusting for age. This association between RV function and LV remodeling was revealed to be an independent one after adjusting for echocardiographic variables.…”
Section: Discussionsupporting
confidence: 50%
“…Notably, the value of sacubitril/valsartan treatment for reversing LV remodeling in patients with HFrEF has been confirmed in recent years. 3,22,23 In our study, we found that the degree of TAPSE improvement was closely associated with improvements in LVEF and LVESV after adjusting for age. This association between RV function and LV remodeling was revealed to be an independent one after adjusting for echocardiographic variables.…”
Section: Discussionsupporting
confidence: 50%
“…This indicates that ARNI might exert long‐term cardiovascular benefits on female patients, and the exact mechanism remains to be explored. 23 …”
Section: Discussionmentioning
confidence: 99%
“…This correlates to the findings from the PARAGON study 22 that ARNI treatment reduced the primary endpoint (total hospitalization for HF and risk of cardiovascular death) by 27% among female patients with HF with preserved ejection fraction. This indicates that ARNI might exert long‐term cardiovascular benefits on female patients, and the exact mechanism remains to be explored 23 …”
Section: Discussionmentioning
confidence: 99%
“…However, women have been observed to be less likely to receive appropriate prescription, with some studies showing female gender to be independently associated with lower odds of ARNI prescription [34,35]. This data is even more striking in the context subgroup analysis from the PROVE-HF study showing that, when compared to men, women had a more rapid and early reduction in serum N-terminal pro-BNP after ARNI initiation [36]. Furthermore, whilst women and men had similar degrees of reverse left ventricular remodelling after ARNI use, women displayed earlier and more consistent remodelling.…”
Section: Medical Therapymentioning
confidence: 99%